A Seven-Gene Signature to Predict Prognosis of Patients With Hepatocellular Carcinoma - Wang, Junli; Zhang, Qi; Shi, Fukang; Yadav, Dipesh Kumar; Hong, Zhengtao; Wang, Jianing; Liang, Tingbo; Bai, Xueli (Frontiers in Genetics, 2021)
Purpose Hepatocellular carcinoma (HCC) is one of the most prevalent malignant diseases worldwide and has a poor prognosis. Gene-based prognostic models have been reported to predict the overall survival of patients with HCC. Unfortunately, most of the genes used in earlier prognostic models lack prospective validation and thus, are not being able to use in clinical practice. Methods Candidate genes were selected from GEPIA (Gene Expression Profiling Interactive Analysis) and their associations with patients’ survival were confirmed by RT-PCR using cDNA tissue microarrays established from patients with HCC after radical resection. A multivariate Cox proportion model was used to calculate the coefficient of corresponding gene. The expression of seven genes of interest (MKI67, AR, PLG, DNASE1L3, PTTG1, PPP1R1A, TTR) with two reference genes was defined to calculate a risk score which determined groups of different risks. Results Our risk scoring efficiently classified patients (n = 129) with HCC into a low, intermediate, and high-risk group. The three groups showed meaningful distinction of 3-year overall survival rate, i.e. 88.9%, 74.5%, and 20.6% for a low, intermediate, and high-risk group, respectively. The prognostic prediction model of risk scores was subsequently verified using an independent prospective cohort (n = 77) and showed high accuracy. Conclusions Our 7-gene signature model performed excellent long-term prediction power and provided crucially guiding therapy for patients who are not a candidate for surgery.